# Thread: Graph of the Related Function

1. ## Graph of the Related Function

I need help solving this problem, can anyone do a step by step guide on how to do this?

1) Use the graph of the parent function to describe the graph of the related function.

F(X) = X^2 --> F(X) = 1/3 (X-1)^2 - 2

2. Originally Posted by Brazuca
I need help solving this problem, can anyone do a step by step guide on how to do this?

1) Use the graph of the parent function to describe the graph of the related function.

F(X) = X^2 --> F(X) = 1/3 (X-1)^2 - 2
describe it, as in words?

the -1 shifts the parent function 1 horizontally, 1 unit to the right.
the 1/3 shrinks this shifted function by a factor of 3
finally, the -2 shifts this function vertically down 2 units

F(X) = -(square root of 2) - 3

4. Originally Posted by Brazuca

F(X) = -(square root of 2) - 3
that question is incomplete, where is the parent function? where is the new function? did you notice you only have a constant there? there's no x

5. Originally Posted by Jhevon
that question is incomplete, where is the parent function? where is the new function? did you notice you only have a constant there? there's no x
Ohh, oops I am having too much stuff to study; I dint notice.

F(X) = (square root of X) --> F(X) = - (square root of X) - 3

6. Originally Posted by Brazuca
Ohh, oops I am having too much stuff to study; I dint notice.

F(X) = (square root of X) --> F(X) = - (square root of X) - 3
if $f(x) = \sqrt {x}$ then $-\sqrt {x} - 3 = -f(x) - 3$.

how do you think we shifted the old graph to get the new one?

7. Originally Posted by Brazuca
I need help solving this problem, can anyone do a step by step guide on how to do this?

1) Use the graph of the parent function to describe the graph of the related function.

F(X) = X^2 --> F(X) = 1/3 (X-1)^2 - 2
Here are the graphs.

8. Originally Posted by Brazuca
Ohh, oops I am having too much stuff to study; I dint notice.

F(X) = (square root of X) --> F(X) = - (square root of X) - 3
Here are the graphs.